HUMAN RESOURCES MANAGEMENT INNOVATION FOR INCREASING PRODUCTIVITY DURING THE COVID-19 PANDEMIC: A NARRATIVE REVIEW - Yuliana, Yuliana (UNIVERSITAS NEGERI SURABAYA, 2022)
This paper is a narrative review. It aims to describe the innovation of human resources management to increase productivity during the COVID-19 pandemic. This is a narrative literature review. The literature was selected from Science Direct, and Google Scholar. The keywords were COVID-19, human resources, innovative, management, productivity. After screening by the title, abstract, and full text, there were 20 eligible articles. The innovative human resources management needs adaptation, resilience, and continuous curiosity to increase productivity and solve problems. Employee engagement in the global network will increase productivity during the COVID-19 pandemic. This paper has limited data because it is not a meta-analysis. This paper is useful for giving information about how to determine an innovative strategy for human resources management to increase productivity during the COVID-19 pandemic.